The role of transformation networks in the process of innovation: Case studies on the discovery and commercialization of innovation - Vitoreli, Marinez Cristina [UNESP]; Gobbo, Jose Alcides [UNESP] (FapUNIFESP (SciELO), 2013)
Innovation is widely recognized as important. In addition, in this context, innovation networks have gained importance in academic studies, since an organization alone, does not always have access to all necessary resources. Gobbo Junior and Olsson (2010) proposed a model of network innovation whereby the transformation networks would be the linking structures between exploration and exploitation networks. In this context, this paper presents two case studies of innovation networks, aiming to increase the understanding on transformation networks. The objective was to understand how they interconnect exploration and exploitation networks; the main actors present in this interface; and to evaluate whether these actors can act as agents, to accelerate the innovation process. It was possible to verify how the transformation networks interconnect exploration and exploitation, and identify the practices and their main actors.
O papel das redes de transformaçáo no processo de inovaçáo: Estudos de caso sobre a descoberta e a comercializaçáo da inovaçáo
Keywords: Exploration and exploitation networks; Innovation; Models of innovation in networks; Network theory